Assessing the quality of studies supporting genetic susceptibility and outcomes of ARDS - Acosta-Herrera, Marialbert; Pino-Yanes, Maria; Perez-Mendez, Lina; Villar, Jesus; Flores, Carlos (Frontiers in Genetics, 2014)
The acute respiratory distress syndrome (ARDS) is a severe inflammatory disease manifested as a result of pulmonary and systemic responses to several insults. It is now well accepted that genetic variation influences these responses. However, little is known about the genes that are responsible for patient susceptibility and outcome of ARDS. Methodological flaws are still abundant among genetic association studies with ARDS and here, we aimed to highlight the quality criteria where the standards have not been reached, to expose the associated genes to facilitate replication attempts, and to provide quick-reference guidance for future studies. We conducted a PubMed search from January 2008 to September 2012 for original articles. Studies were considered if a statistically significant association was declared with either susceptibility or outcomes of all-cause ARDS. Fourteen criteria were used for evaluation and results were compared to those from a previous quality assessment report. Significant improvements affecting study design and statistical analysis were detected. However, major issues such as adjustments for the underlying population stratification and replication studies remain poorly addressed.